Stand Up, Students! Decisional Cues Reduce Sedentary Behavior in University Students - Carina Mnich; Philip Bachert; Jule Kunkel; Hagen Wäsche; Rainer Neumann; Claudio R. Nigg (Frontiers Media S.A., 2019)
Background: University students are prone to sedentary behavior (SB) which is associated with multiple negative health outcomes. Sit-stand desks may allow for a reduction of SB through standing bouts. To promote standing in university students, decisional cues might be a low-cost approach that can easily be implemented.Purpose: To investigate the effects of decisional cues on students' SB, standing, and active behavior.Method: Over 3 weeks, students were observed in a building on a German university campus, which provides sit-stand-desks in study areas, using an adapted version of the SOPLAY protocol. Baseline data was collected in the first week (T1), before posters and table plaques containing decisional cues were set up in the study areas. Effects were measured in the following 2 weeks (T2 and T3).Results: 2,809 (33% female) students were observed. Sitting decreased from 92.9% [SD = 14.9] to 84.5% [SD = 22.1] from T1 to T3 [F(1, 141) = 15.6; p < 0.01; η2 = 0.10]. Standing increased from 5.6% [SD = 13.5] to 10.9% [SD = 14.4] [F(1, 141) = 9.0; p < 0.01; η2 = 0.06] and being active from 1.5% [SD = 6.9] to 4.5% [SD = 14.8] from T1 to T3 [F(1, 141) = 4.2; p < 0.05; η2 = 0.03). Main effect analyses revealed more students standing in the afternoon compared to morning and lunchtime [F(2, 140) = 3.2; p < 0.05; η2 = 0.04).Discussion: Decisional cues could decrease students' SB and promote standing or being active as alternatives. Future research should use a more rigorous study design. The content of the decisional cues should be explored more and expanded to other health promotion areas on campus.